PERCEPCIÓN SOBRE LOS MEDIOS DE COMUNICACIÓN UDEA_2009 - Aigneren, Miguel; Agudelo, Gabriel; Castaño, Olga; Correa, Elena; Levy, Gabriel; Chica, Wilson (La Sociología en sus Escenarios, 2010)
Abstract. The main purpose of this research was to investigate on the receptivity, acceptability, motivation and expectations of the people and receiving public of the communicational products that are realised in the University of Antioquia, in three of the application fields: it press, broadcasting and television. Resumen. Indagar sobre la receptividad, aceptabilidad, motivación y expectativas del público usuario y receptor de los productos comunicacionales que se realizan en la Universidad de Antioquia, en tres de los campos de aplicación: prensa, radiodifusión y televisión.